(untitled) - Plumb, Donald C. (Ames, Iowa,Stockholm, Wis., 2008)
The Sixth Edition of this bestselling handbook includes over 70 new drug monographs, as well as updated dosages and information for older monographs. A separate section on topical medications has been added, and sections on ophthalmic drugs and small animal therapeutic diets have been updated. Completely new to the Sixth Edition is a two-color format and new monograph layout, which enables faster access to much-needed information. The Sixth Edition features new overdose information from the ASPCA Animal Poison Control Center on 50 of the drugs most commonly associated with animal overdoses, and a new appendix on overdose decontamination.
Keywords: Veterinary drugs,Veterinary Drugs,Drug Therapy; Therapeutic use,Veterinary